Stroke profile and care during the COVID-19 pandemic: What changed and what did not? A prospective cohort from Joinville, Brazil - dos Reis, Felipe Ibiapina; de Magalhães, Pedro Silva Correa; Diegoli, Henrique; Longo, Alexandre Luiz; Moro, Carla Heloisa Cabral; Safanelli, Juliana Antunes; Nagel, Vivian; Lange, Marcos Christiano; Zétola, Viviane Flumignan (Frontiers in Neurology, 2023)
Introduction: The COVID-19 pandemic has wrought negative consequences concerning quality of care for stroke patients since its onset. Prospective population-based data about stroke care in the pandemic are limited. This study aims to investigate the impact of COVID-19 pandemic on stroke profile and care in Joinville, Brazil. Methods: A prospective population-based cohort enrolled the first-ever cerebrovascular events in Joinville, Brazil, and a comparative analyzes was conducted between the first 12 months following COVID-19 restrictions (starting March 2020) and the 12 months just before. Patients with transient ischemic attack (TIA) or stroke had their profiles, incidences, subtypes, severity, access to reperfusion therapy, in-hospital stay, complementary investigation, and mortality compared. Results: The profiles of TIA/stroke patients in both periods were similar, with no differences in gender, age, severity, or comorbidities. There was a reduction in incidence of TIA (32.8%; p=0.003). In both periods, intravenous thrombolysis (IV) and mechanical thrombectomy (MT) rates and intervals from door to IV/MT were similar. Patients with cardioembolic stroke and atrial fibrillation had their in-hospital stay abbreviated. The etiologic investigation was similar before and during the pandemic, but there were increases in cranial tomographies (p=0.02), transthoracic echocardiograms (p=0.001), chest X-rays (p<0.001) and transcranial Doppler ultrasounds (p <0.001). The number of cranial magnetic resonance imaging decreased in the pandemic. In-hospital mortality did not change. Discussion: The COVID-19 pandemic is associated with a reduction in TIA, without any influence on stroke profile, the quality of stroke care, in-hospital investigation or mortality. Our findings show an effective response by the local stroke care system and offer convincing evidence that interdisciplinary efforts are the ideal approach to avoiding the COVID-19 pandemic's negative effects, even with scarce resources.